Komunikasi Kepala Sekolah Menengah Atas Kota Lubuklinggau dalam Melakukan Blusukan - Donni Pestalozi; Endang Suswati; Ahmad Gawdy Prananosa (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine the communication of high school principals in Lubuklingga city when conducting blusukan. This research uses a qualitative approach with a phenomenological method, with the research subjects being the School Principal, Teacher Council, and School Staff. The data collection techniques used are observation, interviews, and documentation. From the research, it was found that the communication carried out by the school principal in carrying out blusukan was conveying messages to subordinates in language that was easy to understand and also paying attention to the condition of the subordinates, carrying out two-way communication, using verbal, non-verbal and interpersonal communication so that the principal received appropriate and accurate information. When conducting a blusukan, the information collected during the blusukan can be used as a basis for the school principal to make decisions. In conclusion, the blusukan carried out by the school principal must use good communication so that the results of the blusukan can be used as a basis for the school principal in making decisions. Keywords: blusukan, communication, school principal Membangun komunikasi yang baik sangatlah penting dalam menjalankan roda organisasi sekolah, dengan komunikasi, maka akan terjadi dialogis antara bawahan